Psychological Flexibility and Resilience as Teacher’s Health Factors in Relation to the Ethics of Care - Klon, Weronika; Waszyńska, Katarzyna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
This article aims to examine the concepts of resilience and psychological flexibility in relation to the tasks faced by today’s teachers. It also probes the correlation between resilience and psychological flexibility. Another area of study was to check whether there are any differences in the results obtained on the scales of resilience and psychological flexibility between male and female teachers. The following tools were used in this study: the Acceptance and Action Questionnaire in the second version (AAQII) in the Polish adaptation to measure psychological flexibility, the Resilience Assessment Questionnaire (KOP–26) to examine the level of resilience and a questionnaire of sociodemographic data of our design. The obtained results were subjected to statistical analysis according to the adopted quantitative nature of the research. The study group consisted of 87 female and male teachers of primary schools in the city and commune of Swarzędz. Statistically significant differences were observed in the scores obtained by men and women in the area of the general resilience factor and the family relations subscale. Correlations were also marked between flexibility and resilience in the group of female elementary school teachers surveyed. This is extremely important from a pedagogical perspective for the following reasons. In Carol Gilligan’s theory, feminist morality is based on the ethics of care and responsibility. Similar values are indicated by researchers working on the concept of psychological flexibility as a component of health in social terms. The above observations lead us to the reflection that the current educational system based on values such as competition and hierarchy is not necessarily conducive to the mental health of school communities. A deeper reflection on the social values of responsibility and care in the didactic and educational system could prove useful in the context of caring for the health of individuals and societies.